The benefits and safety of a virtual reality intervention in patients suffering from acute and chronic pain: A pilot study - Bingjie Ma; Libo Zhang; Yun Ji; Xuehua Huang; Luandi Yao; Wei Cheng; Li Hu; Xuejing Lu; Ke Ma (Digital Health)
Background To overcome the challenge of psychotherapist scarcity in applying pain psychotherapy in clinical practice, we developed a virtual reality (VR) program delivering weeks of pain psychotherapy without psychotherapists, with a focus on minimizing the risk of motion sickness. Objectives We conducted a single-arm pilot study to assess the efficacy and motion sickness associated with a VR session delivering guided imagery and breathing techniques selected from the initial course of our VR program, involving patients suffering from various acute and chronic pain. Methods Patients underwent a 15-min VR session. Pain-related and anxiety ratings using a 0–10 numerical rating scale were collected pre-, during-, post-VR and in 6-h follow-up. Motion sickness symptoms were assessed using Simulator Sickness Questionnaire pre- and post-VR. Results Patients ( n  = 73) reported their perceived pain intensity and anxiety reduced significantly from pre- to post-VR by 22.9% and 45.0% (all p  < 0.0001), respectively. Such modulatory effects of VR in pain perception and anxiety persisted at 30 min, 1 h, 2 h, and 6 h post-VR (all p  < 0.0001). The pre-post beneficial effects of VR were independent from patients’ demographic characteristics and their pain duration. Importantly, only six patients (8.2%) had post-VR motion sickness symptoms, and only one patient reported moderate level of severity. Conclusion These findings suggest the selected VR session delivering pain psychotherapeutic techniques may be effective and tolerable for patients with varying pain conditions, which provides initial evidence for the development of future randomized controlled trials of the complete VR program.